Microsatellite markers based genetic diversity and differentiation of Balangir goat population of Odisha - SHARMA, REKHA; AHLAWAT, SONIKA; KHADSE, JAYANT; SONAWANE, DHIRAJ KUMAR; AGGARWAL, RAK; TANTIA, M S (The Indian Journal of Animal Sciences, 2021)
This study was executed to investigate the genetic diversity of Balangir, a local goat population from Odisha, and its differentiation from the geographically closest registered goat breeds, Ganjam and Black Bengal by utilizing 22 polymorphic microsatellite markers. The genotypic status of individuals at each locus was identified by an automated DNA sequencer and allelic data was analyzed for genetic diversity parameters. It resulted in the acquisition of original and comparable information confirming the genetic distinctness of the Balangir goat population. The observed number of alleles varied between 4 (RM4) and 16 (OMHC1) with 8.23±0.64 alleles per locus in Balangir goats. A moderate level of observed heterozygosity (0.57±0.05) indicated sufficiently existing genetic diversity in this goat population which varied between 0.09 (OarJMP29) and 1 (ILSTS22). Expected heterozygosity (0.64±0.04) oscillated between 0.18 (ILSTS34) and 0.89 (OMHC1). Within the population, heterozygosity deficiency estimate (FIS) was significantly positive (0.13±0.05) and 73% of the investigated loci contributed towards the homozygote excess. Consequently, significant deviation from Hardy–Weinberg equilibrium was observed at 12 of 22 analyzed loci. Assessment of Balangir goat population for mutation drift equilibrium indicated that the population did not suffer a reduction in effective population size in the last few generations. Four different approaches utilized to study genetic relationships (F statistics, analysis of molecular variance, phylogenetic relationship genetic distance, and individual assignment) indicated that the Balangir goat population was genetically differentiated from the two registered goat breeds. The study highlighted that Balangir is discrete Indian goat germplasm with sufficient genetic variability and needs to be registered as a goat breed of India.